Assembly of BaTiO3 Nanocrystals into Macroscopic Aerogel Monoliths with High Surface Area1. Issue 26 (22nd May 2014) - Rechberger, Felix; Heiligtag, Florian J.; Süess, Martin J.; Niederberger, Markus
Abstract Aerogels with their low density and high surface area are fascinating materials. However, their advantageous morphology is still far from being fully exploited owing to their limited compositional variety and low crystallinity. Replacing the sol–gel process by a particle‐based assembly route is a powerful alternative to expand the accessible functionalities of aerogels. A strategy is presented for the controlled destabilization of concentrated dispersions of BaTiO3 nanoparticles, resulting in the assembly of the fully crystalline building blocks into cylindrically shaped monolithic gels, thereby combining the inherent properties of ternary oxides with the highly porous microstructure of aerogels. The obtained aerogels showed an unprecedentedly high surface area of over 300 m2 g−1.